IMPLEMENTATION OF THE ETHNO-STEM APPROACH ( SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS ) IN SCIENCE LEARNING TO IMPROVE CRITICAL THINKING SKILLS AND INTEREST OF STUDENTS - Noviana Noor Laily; Ulya Fawaida (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
Education must be able to arouse students' curiosity , so that they can minimize knowledge misconceptions in science learning. There is a need to adapt appropriate learning models in teaching as part of the teacher's responsiveness in learning in accordance with current developments. The provisions that must be provided by students must be in accordance with the skills required by the education market share. Research objectives This is For enhancement Skills think critical and interested participant educate in science learning with use approach Ethno -STEM. Type of research used in study This that is study field research with approach quantitative . The sampling technique uses technique probability sampling . Deep data collection methods study This includes methods , questionnaires , and observations . Data analysis applied to research This is inferential data analysis . Inferential data analysis using the N-Gain test for measure enhancement Skills think critical participant educate . The research results are in the form of integration principle enthology and STEM concepts with seven characteristics main , among others is involve context wisdom local , learning based problem , involvement participant education , critical thinking , collaboration and teams , use technology , as well emphasis on the scientific process . Implementation approach Ethno -STEM is effective in increase Skills think critical and interested Study participant educate especially in class experiment . Teacher response to approach can classified as response good , the teacher response was 51.6% % which influenced response Good participant educate as much as 58.1%. By overall , approach Ethno -STEM can become method effective learning in learning science subjects ..